Diphyllobothriidae Infection in three dogs - Sirigireddy Sivajothi,; Bhavanam Sudhakara Reddy,; Gungi Saritha, (Indian Journal of Veterinary Medicine, 2024)
Diphyllobothriosis, a parasitic infection caused by broad or fish tapeworms, has been increasingly observed in non-endemic regions of Andhra Pradesh. Three dogs were identified suffering with diarrhoea, loss of appetite, vomiting, chronic weight loss, and abdominal distention. Microscopic examination of their faces identified elliptical to oval-shaped, operculated eggs characteristic of the Diphyllobothriidae family.  Serum biochemistry revealed low cobalamin levels (117±14.29 ng/L) in these dogs compared. The dogs were treated with praziquantel and all the dogs showed clinical improvement.